Continuing Education of Employees of Law Enforcement Bodies in the Light of Competence Approach - V. V. Vasilyev (Научный диалог)
The article is devoted to the role of the competence approach in the educational activity of higher educational institutions of the system of educational organizations of the Ministry of Internal Affairs of the Russian Federation as a method of leveling the problematic issues arising in the framework of the implementation of the continuing education model for employees of various services and divisions of territorial bodies of internal affairs. The material for this study is based on the monographic studies on the issues of continuing education, training of police officers and a competent approach to training. The work shows that the continuing educational and training impact on employees of law enforcement bodies who received professional education in educational organizations of the Ministry of Internal Affairs of Russia, most effectively promotes the formation of professional and professional-specialized law enforcement skills. The issue of the need for a full-fledged functioning of the model of continuing education of employees of law enforcement bodies in departmental educational organizations is discussed in the article. Special attention is paid to the analysis of a supplementary law-enforcement vocational education. It is pointed out that such a component, as an increase in professional skill, is mandatory for the active police officer during the entire period of his law enforcement service. The review of economic-legal and sociological opinions on the problem of continuing education in our country is completed. The author dwells upon the perspectives of the competence approach in the continuing educational process of educational organizations of the Ministry of Internal Affairs of Russia.